The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.36660/ijcs.20200174
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity, Obesity, and COVID-19: What can we Expect from his Relationship?

Abstract: The COVID-19 pandemic is a public health problem, whose first cases were found in Wuhan, China, in December, 2019, and which is currently present around the world. 1 COVID-19 is caused by the new coronavirus (SARS-CoV-2), which shows a high potential of contamination. Its transmission occurs through droplets during unprotected proximity with an infected person and contact with contaminated environmental surfaces, which are the main systemic and respiratory symptoms. 1,2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A previous study reported that hospitalized patients with COVID-19 showed higher values of fat mass and body fat percentage when compared to individuals who manifested the mild form with the same BMI ( Lemos et al, 2022 ). Given this and supporting this perspective, regular physical exercise and healthy nutrition can help control these parameters and favor a better immune response against COVID-19 infection ( Queiroz et al, 2022 ), regardless of disease symptomatology. Nonetheless, no significant BMI reductions or body composition improvements were observed at the end of the 8 weeks.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A previous study reported that hospitalized patients with COVID-19 showed higher values of fat mass and body fat percentage when compared to individuals who manifested the mild form with the same BMI ( Lemos et al, 2022 ). Given this and supporting this perspective, regular physical exercise and healthy nutrition can help control these parameters and favor a better immune response against COVID-19 infection ( Queiroz et al, 2022 ), regardless of disease symptomatology. Nonetheless, no significant BMI reductions or body composition improvements were observed at the end of the 8 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…Despite not reducing the risk of infection by COVID-19, reducing body weight seems to be a protective measure against the worsening of COVID-19 disease, as it reduces the inflammatory processes caused by obesity ( Queiroz et al, 2022 ). A previous study reported that hospitalized patients with COVID-19 showed higher values of fat mass and body fat percentage when compared to individuals who manifested the mild form with the same BMI ( Lemos et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%